Design and Control of Double Interleaved Isolated Sepic for High Voltage Gain Dc/Dc Applications - Valdivia-Lefort, P (Institute of Electrical and Electronics Engineers Inc., 2024)
This paper presents a double interleaved doubler isolated single-ended primary-inductor converter (DVDiSEPIC) designed for high voltage gain in fuel cell systems. Featuring an Input-Parallel Output-Series (IPOS) architecture, the converter achieves significant voltage gain, reduced MOSFET voltage stress, and enhanced efficiency with soft switching. Using a high-frequency transformer and Voltage Doubler (VD) cell, the DVDiSEPIC achieves a voltage gain of 21 under ideal conditions. A cascaded closed-loop control strategy with ProportionalIntegral (PI) controllers ensures robust voltage regulation. Comparative analysis highlights the converter s advantages in simplicity and performance. © 2024 IEEE.